A systematic review on molecular, bio-chemical, and pathophysiological mechanisms of yoga, pranayama and meditation causing beneficial effects in various health disorders - Smitha R Varne; Balaji P A (Indian Journal of Integrative Medicine, 2024)
Background: Yoga is a psycho-somatic-spiritual discipline which includes changes in mental attitude, diet, and the practice of specific techniques such as yoga asanas (postures), breathing practices (pranayama’s), and meditation to attain the highest level of consciousness. Since last two decades, there has been a surge in the research on yoga, and it is well established that regular practice of yoga, pranayama and meditation positively impacts overall health and diseases. But still, there is criticism that yoga has not much biological underpinnings. Objectives: This article was designed to present a comprehensive systematic review of the literature regarding the mechanisms of yoga, pranayama, and meditation on a variety of health disorders. Materials and Methods: A Medline search was done in Google chrome to review relevant articles in English literature on yoga articles focusing on the molecular, biochemical, and pathophysiological mechanisms of physiological effects of yogic practices. Data were extracted, constructed; issues were analyzed. Results and Conclusion: 89 articles (17 RCTs, 32 observational/interventional, 27 review/systematic/meta-analysis, 4 text books, 3 guidelines/ consensus statement, 6 unclassified articles) full filled the eligibility criteria, demonstrated the Physiological mechanisms by which yoga, pranayama and meditation resulting in beneficial effects in various neuropsychological, cardiovascular, respiratory, gastrointestinal, Endocrine/reproductive, and other disorders. We recommend future studies on yoga, pranayama and meditation to not only depict clinical health benefits but also simultaneously elucidate the possible physiological mechanisms behind such benefits.